2020
DOI: 10.3390/nu12051465
|View full text |Cite
|
Sign up to set email alerts
|

Best Evidence to Best Practice: Implementing an Innovative Model of Nutrition Care for Patients with Head and Neck Cancer Improves Outcomes

Abstract: Malnutrition is prevalent in patients with head and neck cancer (HNC), impacting outcomes. Despite publication of nutrition care evidence-based guidelines (EBGs), evidence–practice gaps exist. This study aimed to implement and evaluate the integration of a patient-centred, best-practice dietetic model of care into an HNC multidisciplinary team (MDT) to minimise the detrimental sequelae of malnutrition. A mixed-methods, pre–post study design was used to deliver key interventions underpinned by evidence-based im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 35 publications
(36 reference statements)
1
40
0
1
Order By: Relevance
“…The benefits of successful implementation of evidence-based nutrition care in line with best-practice in high-risk tumor groups are now well-documented. Australian-led implementation studies have demonstrated adherence to an evidence-based schedule of dietitian visits throughout treatment for HNC and recovery leads to improved outcomes for patients including nutritional status, weight maintenance, quality of life, treatment completion, and unplanned admissions [ 37 , 38 , 47 ]. Britton et al [ 37 , 48 ] and McCarter et al [ 47 , 49 ] uniquely demonstrated that dietitian-led delivery of motivational interviewing and cognitive behavioral therapy as part of an Eating as Treatment (EAT) intervention improved a range of patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The benefits of successful implementation of evidence-based nutrition care in line with best-practice in high-risk tumor groups are now well-documented. Australian-led implementation studies have demonstrated adherence to an evidence-based schedule of dietitian visits throughout treatment for HNC and recovery leads to improved outcomes for patients including nutritional status, weight maintenance, quality of life, treatment completion, and unplanned admissions [ 37 , 38 , 47 ]. Britton et al [ 37 , 48 ] and McCarter et al [ 47 , 49 ] uniquely demonstrated that dietitian-led delivery of motivational interviewing and cognitive behavioral therapy as part of an Eating as Treatment (EAT) intervention improved a range of patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The remainder of the adherence criteria are reported as a proportion of included patients and by participating site. The optimum degree of adherence to EBGs has not been determined; however, adherence rates of 80% to set criteria has been proposed [ 14 ] and applied in recent studies [ 37 , 38 ]. In this study, adherence to EBG recommendations was categorized as good (≥80%), moderate (≥60 to 80%) and poor (60%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This VRP group developed a Value Framework (VF) with specific projects identified under each of the three pillars of evidence-based care, care management, and care after cancer, as shown in Figure 1 . These pillars are derived from the key components identified in the medical oncology home and OCM models as well as several value-based payer initiatives which have shown value [ 6 , 7 , 8 , 11 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. A full discussion of our value-based care initiative is beyond the scope of this paper; however, we present our value framework and highlights of several other key projects within the framework to show the interdependence of those projects in advancing the implementation and evolving outcome analytics of multidisciplinary oncology pathways.…”
Section: Prioritizing Care Model Redesign For Value-based Cancer Cmentioning
confidence: 99%
“…Oncology pathways are a major component of these programs, with studies of implemented pathway programs showing equal or improved outcomes with lower costs in medical oncology [ 12 , 13 , 14 , 15 , 16 , 17 ], as well as in other disciplines including surgery, radiation oncology, supportive care, and end of life [ 18 , 19 , 20 , 21 , 22 , 23 ]. The evaluation and adoption of oncology pathways were further stimulated by Center for Medicare and Medicaid Services (CMS)’s oncology care MIPPs and Oncology Care Model (OCM) alternate payment programs and private payer pilots with academic and community-based networks and various private payors [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introduction: Multidisciplinary Oncology Pathways Are a Fmentioning
confidence: 99%